Dual-Wavelength Passively Mode-Locked Yb-Doped Fiber Laser Based on a SnSe2-PVA Saturable Absorber - Qiongyu Hu; Ming Li; Ping Li; Zhaojun Liu; Zhenhua Cong; Xiaohan Chen (IEEE Photonics Journal, 2019)
In this letter, tin diselenide (SnSe2) was successfully prepared with the liquid-phase exfoliation method and embedded into polyvinyl alcohol as a saturable absorber (SA) in a dual-wavelength passively mode-locked Yb-doped fiber laser. Stable mode-locked pulses with a maximum average output power of 2.55 mW and a slope efficiency of 1.3% at the fundamental repetition rate of 333 kHz were achieved. By properly adjusting polarization state, four kinds of dual-wavelength fundamental frequency mode-locked pulses with peak wavelength intervals of 0.4, 1.0, 1.5, and 1.9 nm were obtained, and the corresponding waveforms with different single-pulse shapes were investigated in our work. A maximum signal-to-noise ratio of 71.04 dB indicates that SnSe2 is promising to serve as a SA in passively mode-locked fiber lasers.